Catheter ablation or medical therapy to delay progression of atrial fibrillation: the randomized controlled atrial fibrillation progression trial (ATTEST) - Kuck, Karl-Heinz; Lebedev, Dmitry S; Mikhaylov, Evgeny N; Romanov, Alexander; Gellér, László; Kalējs, Oskars; Neumann, Thomas; Davtyan, Karapet; On, Young Keun; Popov, Sergey; Bongiorni, Maria Grazia; Schlüter, Michael; et al. (Europace (London, England), 2021)
Abstract Aims Delay of progression from paroxysmal to persistent atrial fibrillation (AF) is an important measure of long-term success of AF treatment. However, published data on the impact of catheter ablation on AF progression are limited. This study evaluates whether radiofrequency (RF) catheter ablation delays the progression of AF compared with antiarrhythmic drug (AAD) treatment using current AF management guidelines. Methods This prospective, randomized, controlled, two-arm, open-label trial was conducted at 29 hospitals and medical centres across 13 countries. Patients were randomized 1 : 1 to RF ablation or AAD treatment. The primary endpoint was the rate of persistent AF/atrial tachycardia (AT) at 3 years. Results After early study termination following slow enrolment, 255 (79%) of the planned 322 patients were enrolled (RF ablation, n = 128, AAD, n = 127); 36% of patients in the RF ablation group and 41% in the AAD group completed 3 years of follow-up. For the primary endpoint, the Kaplan–Meier estimate of the rate of persistent AF/AT at 3 years was significantly lower with RF ablation [2.4% (95% confidence interval (CI), 0.6–9.4%)] than with AAD therapy [17.5% (95% CI, 10.7–27.9%); one-sided P = 0.0009]. Patients ≥65 years were ∼4 times more likely to progress to persistent AF/AT than patients <65 years, suggesting RF ablation can delay disease progression [hazard ratio: 3.87 (95% CI, 0.88–17.00); P = 0.0727]. Primary adverse events were reported for eight patients in the RF ablation group. Conclusions Radiofrequency ablation is superior to guideline-directed AAD therapy in delaying the progression from paroxysmal to persistent AF.